Transparent microstrip patch antenna using indium tin oxide for telecommunication applications - Hasan, Md. Rashedul; Abdullah, Shabab; Kanon, F. M. Mehedi Hassan; Lakra, Mrittunjoy (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.